Family Physical Economic Strength of Bank Emok Customer: An Analysis the Influence of Debt Behavior, Lifestyle, Economic Pressure, and Family Financial Conditions - Sunarti, Euis; Zammi, Mahfud; Kusumaningrum, Woro Dwi; Fuadah, Rima Syifani (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
Bank Emok is a mobile bank that uses a group mechanism that sits together (emok) every week for debt disbursement and a joint responsibility payment guarantee system. The purpose of this study was to analyze the influence of debt behavior, lifestyle, economic pressure, and family financial conditions (literacy, management, attitudes) on the physical economic strength of Bank Emok customers in Bogor, West Java, Indonesia. This cross-sectional study involved 150 families of Bank Emok customers who were selected by simple random sampling. The research instrument had adequate reliability and validity. The results of the analysis show that there are Bank Emok customer families who are not categorized as poor (71.3% with the Bogor poverty line; 52% with the World Bank poverty line). Quite a large number of wives (63.4%) and husbands (51%) did not complete basic education (12 years). The husband's main job is laborer/employee (47.3%) and 57% of the wives work in various jobs. Debts range from 2-16 million, the average installment per week is 138 thousand. As many as 26.7 percent of families fall into the category of high economic pressure, this is indicated by the difficulty of the family in fulfilling food, education and life skills. The results of the analysis show that the physical economic strength of the family is positively influenced by financial literacy, financial management, attendance mechanisms, the husband's length of education, and family income, and is negatively affected by the husband's age. The analyzed model contributes 27.9 percent to the physical-economic strength of the family. Families need to increase their understanding of basic financial concepts and spending priorities because they play an important role in increasing the physical-economic strength of families.